1999
DOI: 10.1111/j.1574-6968.1999.tb13365.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofcsm1encoding a class V chitin synthase with a myosin motor-like domain from the rice blast fungus,Pyricularia oryzae

Abstract: A gene encoding a chitin synthase with a myosin motor-like domain (csm1) was isolated from Pyricularia oryzae using a PCR fragment amplified from a fungal chitin synthase conserved region. The deduced amino acid sequence of csm1 is homologous to that of CsmA of Aspergillus nidulans (65% identity). The putative gene product of csm1 is consisted of the myosin motor-like domain and a chitin synthase domain as in A. nidulans csmA. The chitin synthase domain of its C-terminus was also homologous to Aspergillus fumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…P. oryzae , the causal agent of rice blast disease, is a filamentous heterothallic Ascomycete with septate hyphae that contains a single nucleus per cell. When P. oryzae infects rice plants, rice blast disease appears as brown spots in ears, leaves, and stems of rice plants and leads to severe damage to the rice plants, resulting in a distinctive reduction of the grain yield. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. oryzae , the causal agent of rice blast disease, is a filamentous heterothallic Ascomycete with septate hyphae that contains a single nucleus per cell. When P. oryzae infects rice plants, rice blast disease appears as brown spots in ears, leaves, and stems of rice plants and leads to severe damage to the rice plants, resulting in a distinctive reduction of the grain yield. …”
Section: Resultsmentioning
confidence: 99%
“…When P. oryzae infects rice plants, rice blast disease appears as brown spots in ears, leaves, and stems of rice plants and leads to severe damage to the rice plants, resulting in a distinctive reduction of the grain yield. [41][42] Figure 2 shows the fungicidal activity of NOAC derivatives against P. oryzae at 0.5%. The results indicated that all of the synthesized compounds were more potent than the original chitosan at the same concentration.…”
Section: Fungicidal Activity Of Synthesized Compounds Against B Cinereamentioning
confidence: 99%
“…The results of an InterProScan analysis (http://www.ebi. ac.uk/ InterProScan/) of the Lechs1 gene product (LeChs1) demonstrated that LeChs1 contains a myosin motor-like domain (MMD) (Fujiwara et al 1997) in the N-terminal region (comprising approximately 603 amino acids, amino acid residues 19 to 621) and a chitin synthase domain (CSD) (Fujiwara et al 1997) terminal MMD and a C-terminal CSD have been isolated and characterized from some fi lamentous, dimorphic and polymorphic fungi that produce true hyphae (Aufauvre-Brown et al 1997;Fujiwara et al 1997;Park et al 1999;Zhang et al 2000;Chigira et al 2002;Müller et al 2002;Epstein 2003, 2006;Madrid et al 2003;Niño-Vega et al 2004;Liu et al 2004;Takeshita et al 2006), and these chitin synthases have been grouped into class V or VI. Comparisons by Clustal W analysis of the deduced amino acid sequence of LeChs1 with those of previously classifi ed class V and class VI chitin synthases (Table 1) suggest the unique character of LeChs1, as mentioned below.…”
Section: Sequencing and Characterization Of Lechs1mentioning
confidence: 99%